2016
DOI: 10.1111/gfs.12234
|View full text |Cite
|
Sign up to set email alerts
|

Canopy characteristics and tillering dynamics of Marandu palisade grass pastures in the rainy–dry transition season

Abstract: The objective of this study was to evaluate the effect of pasture management during the rainy-dry transition season in Jaboticabal, Brazil, on the structural and tillering characteristics of Marandu palisade grass. The treatments were as follows: 15 cm sward height in the rainy season and ungrazed in the rainy-dry transition season (15/0); 25 cm sward height during the rainy season and fixed stocking rate of 2Á5 AU ha À1 during the rainy-dry transition season (25/2Á5); and 35 cm sward height in the rainy seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…Our results were similar to those measured in a site 1200 km from our study (Cerrado region), and documented a value of 6098 kg DM ha −1 11 . However, the values obtained in this study were lower than the 7847 kg DM ha −1 reported in Kenya 12 , and the 9871 kg DM ha −1 reported in Brazil 13 .…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Our results were similar to those measured in a site 1200 km from our study (Cerrado region), and documented a value of 6098 kg DM ha −1 11 . However, the values obtained in this study were lower than the 7847 kg DM ha −1 reported in Kenya 12 , and the 9871 kg DM ha −1 reported in Brazil 13 .…”
Section: Resultscontrasting
confidence: 85%
“…It also differed from the findings measured in a Mata Atlantica region 23 , where a reduction in dead material with increasing nitrogen application rate was observed. Increasing nitrogen application rate diminished the leaf life because of the higher plant growth 13 . The higher amount of dead material reported in this study at the highest nitrogen application rate could be a consequence of the higher stocking rate observed in this treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Pastures maintained stability in tiller density during the trial period, regardless of variations in rainfall. The results corroborate the study by Santana et al (2016), where handling of Marandu palisadegrass at 25 cm of height was considered an appropriate management strategy as it had forage mass which was similar to the best tillering characteristics as when handled at 35 cm.…”
Section: Resultssupporting
confidence: 88%
“…In Brazil, Brachiaria is the most important grass genus for pasture formation (Reis, Bernardes, & Siqueira, 2013;Santana et al, 2017;Santos et al, 2016), within which stands out B. brizantha (Hochst ex.…”
mentioning
confidence: 99%